The Effect Of Mint Leaf Tea And Honey Herbal Medicine On Reducing Emesis Gravidarum In Pregnant Women At The Atikah Community Health Center - Priandini, Irhama (Cattleya Darmaya Fortuna, 2024)
Pregnancy is the growth and development of the fetus. During pregnancy the mother experiences physiological changes, occurring in all organ systems, most of the changes that occur in the mother's body are due to the work of hormones, namely the hormones estrogen and progesterone. During the first trimester of pregnancy, mothers usually complain of nausea and vomiting. Emesis gravidarum is caused by increased levels of estrogen and HCG hormones in the blood, and is also influenced by several factors, one of which is psychosocial factors that predict some women to experience nausea and vomiting in pregnancy, worsening existing symptoms or reducing the ability to cope with normal symptoms. Research Objective: This study aims to determine whether there is an effect of brewing mint leaf tea and honey on reducing emesis gravidarum in first trimester pregnant women at Midwife Atikah, Panyabungan District, Mandailing Natal Regency. Method: The type of research used is Pre-Experimental research. The population in the study were all first trimester pregnant women with nausea and vomiting at Midwife Atikah, Panyabungan District, Mandailing Natal Regency. The sampling technique used Accidental Sampling with a sample size of 30 people. Data collection with PUQE questionnaire sheet instrument Data analysis using Wilcoxon Matched Paired Signed Test with a significant level of p <0.05). Results: The results of the analysis showed that there was an effect with a value of P = 0.001 where P = <0.05. Conclusion: It is recommended that this study can be used as information for pregnant women in TM I at Midwife Atikah, Panyabungan District, Mandailing Natal Regency and it is hoped that pregnant women can consume mint leaf tea and honey as a non-pharmacological drug to reduce emesis gravidarum in pregnant women.